1973
DOI: 10.1159/000180230
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Renal Failure in Infants and Children

Abstract: The definition, causes and management of acute renal failure in children are described. This includes treatment of both specific and nonspecific problems. The specific problems include hyperkalemia, acidosis, sodium control, hypocalcemia, extracellular volume overload, hypertension, seizures and anemia. Supportive treatment is also considered including continuing assessment of the patient’s status, water and calorie requirements, central venous pressure measurements and transport of patients! The indications f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…This was in agreement with Broyer et al in 1971 [7] and Liberman et al in 1972 [8]. However, Counhanan et al in 1975 [9] reported that renal hypoperfusion was the most common etiological factor of ARF.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was in agreement with Broyer et al in 1971 [7] and Liberman et al in 1972 [8]. However, Counhanan et al in 1975 [9] reported that renal hypoperfusion was the most common etiological factor of ARF.…”
Section: Discussionsupporting
confidence: 89%
“…Published data suggested a recovery rate of about 70% and 30% mortality [18]. In our series, 40% died or progressed to chronic renal failure whereas 28% of the Liberman series [8] and 23.6% of Counahan et al series [9] had a similar outcome (Table 3). This outlook for our children was due to those cases who continued to have variable degrees of renal failure rather than mortality.…”
Section: Discussionsupporting
confidence: 54%
“…Numerous publications are available concerning the techniques used, indications for and complications and outcome of paediatric dialysis [1,13,14,16], but little is known about the long-term follow-up after renal function has been regained and acute dialysis has been discontinued. Only a few reports dealing with special entities, such as the haemolytic-uraemic syndrome, have mentioned this prognostic aspect [3,9,10,12,19].…”
Section: Introductionmentioning
confidence: 99%